2010
DOI: 10.22329/amr.v13i2.3022
|View full text |Cite
|
Sign up to set email alerts
|

An Interpersonal Circumplex/Five-Factor Model Analysis Of The Eating Disorders Inventory-3

Abstract: A combined interpersonal circumplex/five-factor model approach was used to investigate personality correlates of Eating Disorders Inventory-3 (EDI-3; Garner, 2004) scales for a non-clinical sample of 234 college women. EDI-3 non-symptom scales and composites had appreciable loadings in the two-dimensional interpersonal circumplex space, with angular locations ranging mainly from Cold (180°) to Submissive (270°). In the five-factor analyses, Neuroticism made significant positive contributions to all of the EDI-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…The former of these two captures factors such as social doubt, distrust and insecurity in relationships and the latter focuses on intrapersonal aspects, characterized by negative self-evaluation and feelings of emptiness and loneliness [32]. Our results are in correspondence with the findings of Brookings and Beilstein [41], who also found that EDI-3 composite scales ineffectiveness and interpersonal problems were associated with the cold and submissive part of the interpersonal circumplex. In our study, the subscale socially inhibited was positively correlated with both ineffectiveness and interpersonal problems and this might strengthen the statement by Carter and colleagues [24] that this subscale might be central to ED pathology and especially in AN (see section IIP in a clinical context).…”
Section: Reliability and Validitysupporting
confidence: 89%
“…The former of these two captures factors such as social doubt, distrust and insecurity in relationships and the latter focuses on intrapersonal aspects, characterized by negative self-evaluation and feelings of emptiness and loneliness [32]. Our results are in correspondence with the findings of Brookings and Beilstein [41], who also found that EDI-3 composite scales ineffectiveness and interpersonal problems were associated with the cold and submissive part of the interpersonal circumplex. In our study, the subscale socially inhibited was positively correlated with both ineffectiveness and interpersonal problems and this might strengthen the statement by Carter and colleagues [24] that this subscale might be central to ED pathology and especially in AN (see section IIP in a clinical context).…”
Section: Reliability and Validitysupporting
confidence: 89%
“…Normative data for the EDE-Q were obtained from Mond et al (2004)—Global: SD 0 = 1.32, α = .96; Restraint: SD 0 = 1.41, α = .83; Eating Concerns: SD 0 = 1.13, α = .83; Weight Concerns: SD 0 = 1.59, α = .86; Shape Concerns: SD 0 = 1.68, α = .93. Normative data for the EDI-3 were obtained from Brookings and Beilstein (2010)—Eating Disorder Risk: SD 0 = 21.4, α = .91; General Maladjustment: SD 0 = 27.7, α = .94. Normative data for the DASS were obtained from Crawford, Cayley, Lovibond, Wilson, and Hartley (2011)—Depression: SD 0 = 3.86, α = .90; Anxiety: SD 0 = 2.78, α = .79; Stress: SD 0 = 4.24, α = .89.…”
Section: Follow-upmentioning
confidence: 99%